Seed dormancy responses to temperature relate to Nothofagus species distribution and determine temporal patterns of germination across altitudes in Patagonia - Arana, María V (The New phytologist, 2016)
© 2015 The Authors. New Phytologist © 2015 New Phytologist Trust.